2008
DOI: 10.1111/j.1440-1584.2008.00953.x
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the health disadvantage of rural populations: How does epidemiological evidence inform rural health policies and research?

Abstract: We reviewed evidence of any apparently significant 'rural-urban' health status differentials in developed countries, to determine whether such differentials are generic or nation-specific, and to explore the nature and policy implications of determinants underpinning rural-urban health variations. A comprehensive literature review of rural-urban health status differentials within Australia, New Zealand, Canada, the USA, the UK, and a variety of other western European nations was undertaken to understand the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
406
4
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 435 publications
(428 citation statements)
references
References 93 publications
(104 reference statements)
9
406
4
9
Order By: Relevance
“…Evidence on associations with regard to rurality is more mixed (Riva et al, 2009). Smith et al (2008), in an international comparative review, note that rurality can link to access to and provision of health services but may not confer health disadvantage, while Midouhas and Flouri (2013) suggest that UK children do not vary in numeracy skills with respect to urban or rural residence but reading age tends to be higher in major urban areas.…”
Section: Our Key Exposure Variables Were Literacy and Numeracy Test Rmentioning
confidence: 99%
“…Evidence on associations with regard to rurality is more mixed (Riva et al, 2009). Smith et al (2008), in an international comparative review, note that rurality can link to access to and provision of health services but may not confer health disadvantage, while Midouhas and Flouri (2013) suggest that UK children do not vary in numeracy skills with respect to urban or rural residence but reading age tends to be higher in major urban areas.…”
Section: Our Key Exposure Variables Were Literacy and Numeracy Test Rmentioning
confidence: 99%
“…Assuming that improving access to nephrology care by reducing travel time would lead to improved outcomes and lower hospitalization rates, as suggested by observational studies (1)(2)(3)(4)(5)(6)(7)(8)(9), establishing this additional clinic would represent good value for money, with ICURs ranging from $4000 to $8000/QALY in most scenarios. However, if reducing distance to specialized care does not reduce the risk of hospitalization or mortality, the cost-effectiveness of establishing a new clinic may be considerably less attractive-although it still might be economically attractive by current standards.…”
Section: Discussionmentioning
confidence: 99%
“…Although kidney disease occurs throughout the province, specialized renal care is provided in 17 clinics that are predominantly located in the more densely populated southern half of Alberta ( Figure 1). Multiple studies (1)(2)(3)(4)(5)(6)(7)(8)(9) have shown that distance from health services is inversely associated with clinical benefits. We recently showed (10) that markers of good-quality care in CKD patients in Alberta decreased with increasing distance from the practice location of the closest nephrologist.…”
Section: Introductionmentioning
confidence: 99%
“…A distribuição da hanseníase na população brasileira é profundamente desigual no que diz respeito aos espaços geográficos e às condições econômicas e sociais, como ocupação, escolaridade e renda 11,12,13 . Alguns estudos apontam que, em geral, os habitantes de áreas rurais não só têm dificuldade em acessar os serviços de saúde, como também recebem diagnós-ticos tardios 14,15 . O ensino médico deve ofertar conteúdos e práticas que promovam a construção de competências profissionais que superem a tríade agente-hospedeiro-ambiente e levem em consideração a complexidade da determinação social das doenças tanto nas populações quanto nos indivíduos 16,17 .…”
Section: Investigação Dos Contatos Intradomiciliaresunclassified